Penggunaan Informasi Pengungkapan Sukarela di Media Sosial: Analisis Technology Acceptance Model (TAM) - Soemarno Hidayatullah S; Nurul Afiqah Annas; Wenni Andriani (Politeknik Ganesha Medan, 2023)
This study aims to analyze the determinants of investor behavior while making investment decisions using voluntary disclosure information obtained from social media pages. Using the technology acceptance model, the correlation between belief constructs and behavioral intentions is measured. Perceived ease of use, perceived usefulness, and perceived enjoyment are the three belief constructs used in this study. 180 employees were respondents, and structural equation modelling partial least square was used to evaluate the hypotheses. The results showed that Indonesian investors believe that information regarding voluntary disclosures provided on social media pages will influence their decision to use such information when making investments. The intention is influenced by perceived ease of use, perceived usefulness, and perceived enjoyment. This study also found that perceived enjoyment has an effect on perceived ease of use and perceived usefulness.